KADAR KREATININ DAN BERSIHAN KREATININ PENDERITA LEPTOSPIROSIS - Ismawati Amin; B. Rusli; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Leptospirosis is a frequent zoonosis in the tropics including Indonesia with 5–30% incidence and 5–20% mortality rate due toacute renal failure (ARF). To determine the frequency of leptospirosis by sex, age and glomerulus’s filtration rate (GFR) of the patient.A retrospective descriptive study on 32 subjects was done by measuring the creatinine clearance using Lyasis Auto analyzer in ClinicalPathology Laboratory of Wahidin Sudirohusodo Hospital from January 2004 to June 2006, of 32 patients, 25 (78%) male and 7 (22%)female, with the most frequent age range from 30–40 years (34.4%). Of the patients, 2 (6.3%) have normal GFR, 6 (18.8%) withmild GFR reduction, 10 (31.3%) with medium GFR reduction, 10 (31.3%) with severe GFR reduction and 4 (12.5%) with acute renalfailure. Leptospirosis is most frequent found in male with age between 30–40 years old. with reduction of GFR from mild to severe, andeven terminated with acute renal failure.